Efforts to Improve Sensory Stimulation in the Elderly Through Therapy Group Activities for the Elderly at the Regional Technical Implementation Unit Tresna Werdha Social Institutions Pagar Dewa Bengkulu - Silvalia Rahma Pratiwi; Susanty, Yunita Ery; Zuraida; Niken Pratiwi; Anggel Ghonyyu (Jurnal Pengabdian, 2025)
Aging is a natural process that every individual experiences. Generally, someone over 60 years of age is considered elderly. Many changes occur in the body, including changes in sensory function. One way to improve sensory function is through Group Activity Therapy (GAT). The goal of sensory stimulation group activity treatment is to elicit a positive reaction from the patient by engaging all five senses. This community service program aims to improve sensory function in the elderly. The implementation method involves measuring sensory function before and after the GAT activity. This activity took place on August 1, 2025, in the Hall of the UPTD (Residential Unit) of the Pagar Dewa Bengkulu Social Welfare Home. The results showed improved sensory function in the elderly after participating in Group Activity Therapy.